2021
DOI: 10.1590/1413-82712021260104
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Internet Use, Emotional Problems and Quality of Life Among Adolescents

Abstract: This study aimed to evaluate the prevalence of Problematic Internet Use (PIU) among adolescents (N = 466) and its possible association with emotional problems and quality of life. Students (Mage = 12.8 years; SD = 1.9) from five public schools in a city in the State of São Paulo participated in this study and completed four instruments: a sociodemographic questionnaire; Internet Addiction Test (IAT); Depression Anxiety Stress Scale (DASS-21) and Pediatric Quality of Life Inventory (PedsQL). No significant diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 19 publications
1
2
0
6
Order By: Relevance
“…In a study conducted in adolescents whose parents were divorced, Van Dijk et al [23] found that problematic internet use is more common particularly among adolescents who stated that they did not feel close to their mothers. In another study of 466 Brazilian adolescents, Andrade et al [24] emphasized that family conflicts and child-parent conflicts cause unhealthy behaviors in children such as problematic internet use and that families should be involved in studies that aim to limit internet use. Say and Durak Batigun [16] also reported that an adolescent's negative relationship with their parents has the effect of increasing problematic internet use.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted in adolescents whose parents were divorced, Van Dijk et al [23] found that problematic internet use is more common particularly among adolescents who stated that they did not feel close to their mothers. In another study of 466 Brazilian adolescents, Andrade et al [24] emphasized that family conflicts and child-parent conflicts cause unhealthy behaviors in children such as problematic internet use and that families should be involved in studies that aim to limit internet use. Say and Durak Batigun [16] also reported that an adolescent's negative relationship with their parents has the effect of increasing problematic internet use.…”
Section: Discussionmentioning
confidence: 99%
“…Em relação à depressão e o uso adicto das redes sociais, esta pesquisa encontrou associação positiva e de magnitude moderada entre os construtos. A literatura indica que a relação entre depressão, ansiedade e engajamento em mídias sociais não necessariamente está atrelada ao aumento de uso das redes sociais, mas ao uso problemático da internet (Andrade et al, 2021;Moromizato et al, 2017). Yoon et al…”
Section: Discussionunclassified
“…Os resultados obtidos demonstraram que não necessariamente o maior uso das redes sociais está associado à ansiedade e depressão, mas sim o uso problemático da internet (Moromizato et al, 2017). O uso problemático da internet é caracterizado pelo uso excessivo da internet e tem sido associado a prejuízos à saúde física e mental, além de piora nos níveis de qualidade de vida, principalmente em jovens, cujos sintomas mais frequentes são vícios comportamentais, tais como preocupação exagerada com o uso da internet, compulsão pelo aumento de tempo de uso, descontrole frente ao uso de internet e indiferença pelas atividades sociais (Andrade et al, 2021).…”
Section: Introductionunclassified
“…Essa classificação foi baseada em estudos prévios da literatura (Andrade et al, 2021;Andrade, Scatena, Bedendo, et al, 2020;Andrade, Scatena, Martins, et al, 2020).…”
Section: Instrumentosunclassified